Penerapan Sistem Informasi Perbankan pada PT Bank Sumut - Melisa Lubis; M. Irwan Padli Nasution (MES Management Journal, 2023)
Technology is an important influence for the progress of a company's information system. This is inseparable from the increasingly sharp competition between banking companies, therefore companies need to apply an information system technology to banks. Information systems in banking aim to provide comfort, convenience and satisfaction to consumers or customers and also for modern information system technology companies capable of improving company operations. The purpose of this study was to find out about the bank information system at PT. SUMUT Bank. The discussion technique used is descriptive method. Data collection techniques were carried out to the library of several scientific books and writings related to the discussions carried out as well as journals related to this thesis. The bank information system at Bank SUMUT is internet banking or what is known as e-Banking. The term e-Banking is making transactions, payments and other transactions via the internet with a bank's website that is equipped with a security system. The advantage of eBanking is that customers do not need to stand in line to make financial transactions. Customers can immediately carry out banking activities at home and anywhere. Apart from that, it also saves time, customers do not need to spend all day just to complete various financial transactions. However, the drawback of this bank information system is that it is prone to burglary. Lost funds often cannot be returned and customers experience losses. Apart from that, there are other disadvantages, namely depending on the internet, it is impossible to carry out e-banking transactions in areas where there is no internet network. It is expected that the internet network speed must also be faster, if the internet network is old then e-Banking will experience transaction failures. Keywords: information system, banking